2019
DOI: 10.3390/ijerph16101798
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mental Health and the Quality of Life of Polish Nurses with Many Years of Experience in the Profession: A Cross-Sectional Study

Abstract: Background: In their professional work, nurses struggle repeatedly with difficult situations that are causes of stress. Another issue is the low prestige of the nursing profession compared with other professions, which results in dissatisfaction, increased frustration, and lack of precision when performing professional tasks. The aim of this study was to assess the relationship between mental health and quality of life and satisfaction with life in nurses with many years of experience in the profession. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
3
15
1
1
Order By: Relevance
“…Abbasi et al (2017) found that nurses over 29 years old had a decreasing QoWL. Previous studies showed that self-reported forgetfulness, sleep disturbances, anxiety and fatigue rose with age (Abbasi et al, 2017;Chen et al, 2014;Lewko et al, 2019). It was also noted that level of physical and cognitive functions declined with age, which could influence nurses' work performance (Abbasi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abbasi et al (2017) found that nurses over 29 years old had a decreasing QoWL. Previous studies showed that self-reported forgetfulness, sleep disturbances, anxiety and fatigue rose with age (Abbasi et al, 2017;Chen et al, 2014;Lewko et al, 2019). It was also noted that level of physical and cognitive functions declined with age, which could influence nurses' work performance (Abbasi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Burnout has been found to impact nurses' ability to deal with negative emotions, nurses' work performance and patient safety (Choi et al, 2018). Nursing care is a detailed work with great responsibility, and it requires nurses to have good physical and psychological states (Lewko, Misiak, & Sierżantowicz, 2019). Nurses with job burnout cannot invest enough energy in clinical work, identify health care error in time and provide safe and quality patient care, which might lead to adverse patient outcomes (Choi et al, 2018;See et al, 2018;Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the social relationships and social support networks are usually related to this aspect of QOL (Helgeson, 2003;Wedgeworth et al, 2017;Zhang & Xiang, 2019) Altogether, those factors represent different aspects of biopsychosocial functioning, including the general health status, familiar and social relationships, as well satisfaction with life and work practice, which are the main predictors of QOL (Rapala et al, 2005). Nonetheless other factors such as the presence of chronic disease and mental disorders may also affect QOL (Lewko et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The nurses' financial situation significantly determined quality of life as well as mental health components, and a higher assessment of negative mental health symptoms pertained to nurses in worse financial situations [22].…”
Section: Discussionmentioning
confidence: 99%